From Sharing to Learning: Informal Religious Education for Muslim Women on Instagram - Larasati, Yuniar Galuh; Fernando, Henky (Indonesian Journal of Islamic Religious Education, 2025)
This study examines how informal religious education for Muslim women is shaped through the dissemination of content on Instagram, focusing on the account @muslimahorid as the primary unit of analysis. Using a qualitative approach grounded in netnography, the study finds that religious learning in digital spaces takes place not only through the verbal delivery of religious materials but also through visual representations, everyday narratives, and user interactions. Religious learning emerges from processes of sharing personal experiences, moral advice, and emotional support that are spontaneously exchanged within the digital sphere. This phenomenon demonstrates that social media can function as a flexible, participatory, and community-based learning environment, where Islamic values and norms are reproduced through a culture of sharing. The study contributes to the development of Islamic education studies by emphasizing the importance of understanding the dynamics of religiosity in the era of new media. Although limited by its focus on a single account, the findings open new directions for future research to explore the transformation of informal religious education across diverse communities and digital platforms.